Low Testosteron Level in Worsening Symptom of Heart Failure Patients: A Literature Review - Ardiansyah, Ryan; Sauqy, Akhmad Sandy (Cardiovascular and Cardiometabolic Journal (CCJ), 2025)
Abstract Background: Heart failure can be caused by a variety of factors, including high blood pressure, coronary artery disease, diabetes, obesity, smoking, and genetics. Testosterone is the primary male hormone responsible for regulating sex differentiation, producing male sex characteristics, spermatogenesis, and fertility. It plays a crucial role in various bodily functions, including the development of male reproductive tissues and the maintenance of muscle mass and bone density. Testosterone levels have been found to be significantly decreased in heart failure patients compared to healthy controls. This suggests that low testosterone levels may play a role in the development or progression of heart failure. The relationship between testosterone and heart failure is complex and warrants further investigation. Additional research is needed to better understand the role of testosterone in heart failure and to determine the optimal therapeutic strategy for its management. Based on these data, we decided to further investigate how low testosterone levels affect the symptoms of heart failure patients. Aims: This literature review study aims to examine further how low testosterone levels affect the symptoms of heart failure patients. Method: Journals in this literature review used three databases, including Google Scholar, PubMed, and Science Direct, using the keywords "testosterone" and "heart failure." The literature search was adjusted based on the inclusion and exclusion criteria. Result: The search results were obtained from 10 international journals. The results showed that testosterone is crucial in maintaining men's health and well-being. Testosterone deficiency was associated with a worsening of HFpEF in men, those with lower testosterone levels had worse symptoms and a lower quality of life. Conclusion: Testosterone exerts an important regulation of cardiovascular function through genomic and nongenomic pathways. It influences contractility, energy metabolism of myocardial cells, apoptosis, and the remodeling process. Reduced testosterone levels in men with heart failure are associated with increased mortality and poor prognosis. -- Highlights: 1. Testosterone deficiency is associated with worsening symptoms and poorer quality of life in men with heart failure with preserved ejection fraction (HFpEF). 2. The role of testosterone in cardiovascular health is multifaceted—its deficiency may contribute to adverse cardiac remodeling, while excessive levels may increase thromboembolic and inflammatory risks.